Role of Basophils in a Broad Spectrum of Disorders - Miyake, Kensuke; Ito, Junya; Karasuyama, Hajime (Frontiers in Immunology, 2022)
Basophils are the rarest granulocytes and have long been overlooked in immunological research due to their rarity and similarities with tissue-resident mast cells. In the last two decades, non-redundant functions of basophils have been clarified or implicated in a broad spectrum of immune responses, particularly by virtue of the development of novel analytical tools for basophils. Basophils infiltrate inflamed tissues of patients with various disorders, even though they circulate in the bloodstream under homeostatic conditions. Depletion of basophils results in the amelioration or exaggeration of inflammation, depending on models of disease, indicating basophils can play either beneficial or deleterious roles in a context-dependent manner. In this review, we summarize the recent findings of basophil pathophysiology under various conditions in mice and humans, including allergy, autoimmunity, tumors, tissue repair, fibrosis, and COVID-19. Further mechanistic studies on basophil biology could lead to the identification of novel biomarkers or therapeutic targets in a broad range of diseases.